Current Operating Procedure (COP) for Bleomycin ElectroScleroTherapy (BEST) of low-flow vascular malformations - Muir, Tobian (Radiology and oncology (Ljubljana), 2024)
Bleomycin ElectroScleroTherapy (BEST) is a new approach in the treatment of vascular malformations. After bleomycin is administered to the malformation, electric pulses are applied to the target area to enhance the effectiveness of bleomycin. The mode of action is comparable to the effect of electrochemotherapy on tumour vasculature. For the wider and safer use of BEST in the clinical treatment of low-flow vascular malformations, this Current Operating Procedure (COP) is being prepared. It is a proposal for the clinical standardisation of BEST using the Cliniporator® as the electrical pulse generator with its associated electrodes. The electrical parameters considered in this protocol are those validated by the European Standard Operating Procedures for Electrochemotherapy (ESOPE) with the Cliniporator®. Conclusions General requirements are proposed, and, depending on the type of lesion, local skills and the availability of radiological equipment, two technical approaches of BEST are described based on ultrasound guided intervention or combined ultrasound and fluoroscopic guided intervention.
Keywords: električni pulzi; elektroskleroterapija z bleomicinom; skleroterapija z bleomicinom; ultrazvok; žilne malformacije nizkega pretoka